2014 Annual Report of the American Association of Poison Control Centers' National Poison Data System (NPDS): 32nd Annual Report. (26th November 2015) - Mowry, James B.; Spyker, Daniel A.; Brooks, Daniel E.; McMillan, Naya; Schauben, Jay L.
ABSTRACT: Background : This is the 32nd Annual Report of the American Association of Poison Control Centers' (AAPCC) National Poison Data System (NPDS). As of 1 January 2014, 56 of the nation's poison centers (PCs) uploaded case data automatically to NPDS. The upload interval was 7.82 [7.02, 11.17] (median [25%, 75%]) minutes, creating a near real-time national exposure and information database and surveillance system. Methodology : We analyzed the case data tabulating specific indices from NPDS. The methodology was similar to that of previous years. Where changes were introduced, the differences are identified. Poison center cases with medical outcomes of death were evaluated by a team of medical and clinical toxicologist reviewers using an ordinal scale of 1–6 to assess the Relative Contribution to Fatality (RCF) of the exposure to the death. Results : In 2014, 2, 890, 909 closed encounters were logged by NPDS: 2, 165, 142 human exposures, 56, 265 animal exposures, 663, 305 information calls, 6, 085 human confirmed nonexposures, and 112 animal confirmed nonexposures. US poison centers (PCs) also made 2, 617, 346 follow-up calls in 2014. Total encounters showed a 5.5% decline from 2013, while health care facility human exposure cases increased by 3.3% from 2013. All information calls decreased by 17.7% and health care facility (HCF) information calls were essentially flat, decreasing by 0.04%, medication identification requests (Drug ID) decreased 29.8%, and human exposures reported to US PCs decreased 1.1%. Human exposures with less serious outcomes have decreased 3.40% per year since 2008 while those with more serious outcomes (moderate, major or death) have increased by 4.29% per year since 2000. The top 5 substance classes most frequently involved in all human exposures were analgesics (11.3%), cosmetics/personal care products (7.7%), household cleaning substances (7.7%), sedatives/hypnotics/antipsychotics (5.9%), and antidepressants (4.4%). Sedative/Hypnotics/Antipsychotics exposures as a class increased the most rapidly (2, 368 calls (12.2%)/year) over the last 13 years for cases showing more serious outcomes. The top 5 most common exposures in children age 5 years or less were cosmetics/personal care products (14.0%), household cleaning substances (11.0%), analgesics (9.3%), foreign bodies/toys/miscellaneous (6.7%), and topical preparations (5.8%). Drug identification requests comprised 43.3% of all information calls. NPDS documented 1, 835 human exposures resulting in death with 1, 408 human fatalities judged related (RCF of 1-Undoubtedly responsible, 2-Probably responsible, or 3-Contributory). Conclusions : These data support the continued value of PC expertise and need for specialized medical toxicology information to manage more serious exposures, despite a decrease in calls involving less serious exposures. Unintentional and intentional exposures continue to be a significant cause of morbidity and mortality in the US. The near real-time, always current status of NPDS represents a national public health resource to collect and monitor US exposure cases and information calls. The continuing mission of NPDS is to provide a nationwide infrastructure for surveillance for all types of exposures (e.g., foreign body, viral, bacterial, venomous, chemical agent, or commercial product), the identification of events of public health significance, resilience, response and situational awareness tracking. NPDS is a model system for the real-time surveillance of national and global public health.